ONLINE VS OFFLINE READING CLASSES: THE EFL UNIVERSITY STUDENTS’ PERSPECTIVES - Nabila Utomo; Dzurriyyatun Ni’mah; Henny Rahmawati (UIBU, 2023)
This qualitative study was conducted to identify the EFL university students' perspectives on online and offline reading classes. This study involved ten English students of the seventh semester, from one of the private universities in Malang who have excellent scores in English reading classes. Using a semi-structured interview, the students were asked about problems, difficulties, advantages, and reading understanding in online and offline classes. The data were analyzed using content analysis. The investigation triangulation was performed by involving two data analysts to triangulate the data. The result found in this study are students frequently experience problems with unstable internet connections, communication difficulties with lecturers, textbook download troubles, and eyestrain from reading online content. Whereas, the advantages are students have more reading sources, have time and reading topics flexibility, and are cost-effective. Moreover, EFL university students' problems or difficulties in offline reading classes are more cost, limitation of reading time and topics, and few reading resources. While the advantages of offline reading classes are enjoyable, interactive, and communicative.